Legal support of palliative care for cancer patients - N. Yu. Chernus; S. V. Sidorov; E. V. Babayants; S. E. Krasilnikov (Сибирский онкологический журнал, 2019)
Background. According to the novel approach to the treatment of patients as persons, the phenomenon of palliation distinguishes modern medicine from the traditional medical paternalism. it means that medical science and practice go beyond physical health, when treatment methods aimed to improving the quality of patient’ life are widely used. man as a phenomenon of culture becomes something much more than his physical body.The purpose of the study was to analyze the palliative care legislation.Results. The palliative care was shown not to be a type of medical care, but it refers to the terms used in clinical practice to determine the purposes of specialized treatment aimed at not curing the disease, but rather extending life and controlling symptoms. conclusion. it is necessary to include patients’ relatives and friends to the number of people in need of medical care. The development of the federal state educational standard of higher education in the specialty of a palliative care physician is also of great importance.